Produção e formulação de pó magnético preto revelador de impressões papilares latentes a partir do caroço de euterpe oleracea, mart e carepa de laminação - FERREIRA, João Gabriel Monteiro (2024)
Fingerprint revealing powder is one of the techniques that make up forensic sciences, and one of the oldest used for human identification. Despite being an easy-to-use and widely applied technique, in Brazil it faces high prices for importing the developer powder, making the technique not economically accessible. Thus, this research seeks to use as raw materials, by- products that have inappropriate disposal or little reuse, so that the developing powder has a more affordable production cost and for the reuse of materials that were previously discarded. Therefore, in the present work we sought to develop a magnetic black powder, from açaí cart, which is a residue resulting from the pulping of the fruit for consumption, and mill scale, which is a post-casting stage by-product originating from industries, and powdered graphite. The developed product was characterized through immediate analyses, Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (SEM/EDS), X-ray Fluorescence (XRF), X-ray Diffractometry (XRD). Subsequently, tests were carried out to verify the quality of the development of Latent Papillary Prints (IPL’s). After the characterizations, it was observed that the formulated powder produced good fingerprint development and can be used satisfactorily as a revealing powder.